Death Penalty Legislation in China and Indonesia Under International Human Rights Law Perspective - Dodik Setiawan Nur Heriyanto; Huang Gui (Jurnal Hukum IUS QUIA IUSTUM, 2016)
Most of countries in the world have terminated the death sentence for the sake of respecting the human rights internationally as the universal human rights. In fact, China and Indonesia have the different practice in the executing the death penalty for certain crimes.  Using the normative legal research method, this research analysed two core issues including to what extent of the international protection of human rights in China and Indonesia. This study is to analyze two main issues: to what extent the international protection of human rights in China and Indonesia and how the law and the international protection of human right impact the policy of implementation of death sentence in China and Indonesia. This study concluded two points: first, there was a difference in the implementation of human rights both in China and in Indonesia particularly in implementing the death sentence in both countries in which both apply certain limitation in implementing the death sentence. Second, the approval of the International Kovenan about the civil right and political right becomes the basic parameter to what extent those two countries regulate the policy of death sentence and to what extent of the attempt of those two countries in making its domestic law harmonious with the international human right.